3D modelling of the mechanical behaviour of magnetic forming systems - Boutana Ilhem; Boussalem Mohamed Elamin; Laouira Ahmed; Bouferroum Salaheddine (Institute of Advanced Engineering and Science, 2022)
High-speed forming methods become attractive in manufacturing and significantly reduce the cost and energy requirements. Electromagnetic forming is a high-velocity pulse forming technique that applies electromagnetic forces to sheet or tubular workpieces using a pulsed magnetic field. In order to understand the physical behaviours of materials, numerical modeling is highly desired. Therefore, in this study, we investigate the mechanical behaviour of the electromagnetic sheet stamping and magnetic tube expansion and compression systems. For these 3D simulations, COMSOL multiphysics software is used. It provides the possibility to model the electromagnetic aspects of the problem along with the thermal and mechanical aspects in a coupled method. The developed 3D numerical fully coupled models lead to analyze the transient magnetic fields, Lorentz forces acting on workpieces, and the plastic deformations obtained in several magnetic forming systems. The effects of systems parameters are also investigated such as the coil’s form and the number of its turns.